Shear behaviour of architectural fabrics subjected to biaxial tensile loads - Colman, A.G.; Bridgens, B.N.; Gosling, P.D.; Jou, G.-T.; Hsu, X.-Y. (Composites. Part A, Applied science and manufacturing, 2014)
Broad assumptions are made in the testing and simulation of architectural fabrics used for tensile fabric structures. In particular, fabric shear behaviour is poorly understood and is not routinely determined. Tensile structures are continuously subject to a combination of biaxial tensile stress and shear stress, yet there is no accepted method for accurately determining shear behaviour in a tensioned fabric. A novel picture frame shear test design and associated test protocol is described here that aims to provide a practicable solution for the accurate determination of the in-situ shear stiffness of architectural fabrics. Results of shear tests on fabrics subjected to increasing levels of biaxial prestress are presented and the implications for analysis are discussed.